Enhanced osteogenic differentiation via chemically engineered aggregation of mouse embryonic stem cells - Gothard, David (2009)
The formation of embryoid bodies has long been utilized to initiate differentiation of embryonic stem cells in vitro. The embryoid body provides an effective means of recapitulating early stages during embryogenesis and formation of the three germ layers. Current methodology for embryoid formation is extensive but exhibits a lack of standardisation and coherence. Here is shown a 3D culure system for controlled embryonic stem cell aggregation via a non-cytotoxic cell surface modification and cell-cell cross-linking. Embryoid body formation was found to be a complex relationship between embryonic stem cell aggregation, proliferation, death, cluster agglomeration, extracellular matrix deposition and structural reorganisation. Engineered embryoid bodies formed more rapidly and were significantly larger than those in control samples. Embryoid body characterisation revealed a layered internal structure resulting from poor nutrient and gaseous diffusion and consequent core necrosis after ≥ 5 days in suspension culture. Immuno-labelling and PCR amplification analysis of Brachyury, Nestin, Gata-4 and Oct-4 showed differentiation of mesoderm, ectoderm and endoderm on the embryoid body surface and internal undifferentiated cells, respectively. Engineering appeared to enhance mesoderm differentiation, a progenitor of the osteogenic lineage. Embryoid bodies in settled culture spread outwards to form a plateau of collagen matrix which was later mineralized through differentiated osteoblast function. Quantification through Alizarin Red stained bone nodules and alkaline phosphatase activity demonstrated osteogenic differentiation enhancement within engineered samples. Dex-loaded poly-(lactic co-glycolic) acid polymer microparticles were found to be an effective method for delivery of osteo-inductive factors to internal undifferentiated embryonic stem cells within the embryoid bodies. These findings show that the proposed 3D culture system provides reliable and repeatable methodology for the controlled formation of embryoid bodies which exhibit enhanced osteogenic differentiation. It is hoped that these engineered embryoid bodies could be used to efficiently generate homogeneous bone tissue for clinical application.